Impact of immunosuppressant therapy on new-onset diabetes in liver transplant recipients - Liu FC; Lin HT; Lin JR; Yu HP (Dove Medical Press, 2017)
Fu-Chao Liu,1,2,* Huan-Tang Lin,1,2,* Jr-Rung Lin,1–3 Huang-Ping Yu1,2 1Department of Anesthesiology, Chang Gung Memorial Hospital, 2College of Medicine, 3Clinical Informatics and Medical Statistics Research Center and Graduate Institute of Clinical Medicine, Chang Gung University, Taoyuan, Taiwan *These authors contributed equally to this work Abstract: This nationwide, population-based study aimed to clarify the effects of immunosuppressive regimens on new-onset diabetes after liver transplantation (NODALT). The National Health Insurance database of Taiwan was explored for patients who received liver transplantation without pre-transplant diabetes from 1998 to 2012. Information regarding clinical conditions and immunosuppressant utilization among these patients was analyzed statistically. Of the 2,140 patients included in our study, 189 (8.8%) developed NODALT. The pre-transplant risk factors for NODALT were identified as old age, male sex, hepatitis C, alcoholic hepatitis, and immunosuppressant use of tacrolimus (TAC). All patients used corticosteroids as a baseline immunosuppressant. The immunosuppressant regimen of cyclosporine (CsA)+TAC+mycophenolate mofetil (MMF) contributed most to NODALT (adjusted hazard ratio 7.596) in comparison with the regimens of TAC+MMF and CsA+MMF; this regimen also contributed significantly to higher post-transplant bacteremia, urinary tract infection, pneumonia, renal failure, and mortality rate. In conclusion, our analysis confirmed TAC-based immunosuppression contributes to higher NODALT incidence than CsA-based regimen, and TAC-CsA conversion due to any causes might lead to worse clinical outcomes. Clinicians should make better risk stratifications before prescribing immunosuppressants for liver transplant recipients. Keywords: new-onset diabetes, liver transplantation, immunosuppressant, population-based study, clinical outcome